Estudo da dissolução in vitro de cloridrato de diltiazem em cápsulas manipuladas - Mendonça, Taciane Ferreira (2010)
Diltiazem hydrochloride is a benzothiazepine calcium channel antagonist, mainly used in the treatment of angina, hypertension and supraventricular arrhythmias and is commercially available in tablets, extended release tablets, immediate release capsules, extended release capsules and injectable dosage forms. At the present moment, there is no official methods described in any pharmacopoeia for the quantification of the drug in immediate release capsules. The aim of this study was to establish dissolution conditions and to validate the analytical methods for diltiazem hydrochloride quantification in pharmaceutical immediate release capsules. Different conditions such as dissolution media (water, 0.1 mol L-1 HCl and pH 6.8 potassium phosphate buffer), apparatus (USP apparatus 1 and 2) and rotation speeds (50, 75 and 100 rpm) were evaluated in order to establish dissolution conditions for 60 mg diltiazem hydrochloride in pharmaceutical capsules. 10 mL sample aliquots were withdrawn at 5, 10, 15, 30 and 60 minutes and replaced. The drug concentrations in dissolution media were determined by both UV spectrophotometry at 237 nm and by a HPLC method, using a Hypersil BDS RP-18 (10.0 cm×4.0 mm), 3 μm particle size column. The mobile phase was acetonitrile-potassium phosphate buffer pH = 6.2- triethylamine (45:55:0.2, v/v/v), at a flowrate of 1.0 mL min-1 and UV detection at 240 nm. The use of potassium phosphate buffer pH 6.8 as dissolution medium, paddle as apparatus at the stirring speed of 50 rpm and 30 minutes of test provided satisfactory results for assessment of dissolution diltiazem hydrochloride immediate release capsules. The described analytical methods and dissolution procedures were validated presenting stability, linearity, selectivity, precision and accuracy. Finally, all the methods were used for quality control assays of the products tests A, B and C, which demonstrated to be in accordance to regulatory demands.